From Christ to Confucius : German missionaries, Chinese Christians, and the globalization of Christianity, 1860-1950 - Wu, Albert Monshan (Yale University Press, 2016)
A bold and original study of German missionaries in China, who catalyzed a revolution in thinking among European Christians about the nature of Christianity itself In this accessibly written and empirically based study, Albert Wu documents how German missionaries--chastened by their failure to convert Chinese people to Christianity--reconsidered their attitudes toward Chinese culture and Confucianism. In time, their increased openness catalyzed a revolution in thinking among European Christians about the nature of Christianity itself. At a moment when Europe's Christian population is falling behind those of South America and Africa, Wu's provocative analysis sheds light on the roots of Christianity's global shift.